On the Construction of Group Equivariant Non-Expansive Operators via Permutants and Symmetric Functions - Conti, Francesco; Frosini, Patrizio; Quercioli, Nicola (Frontiers in Artificial Intelligence, 2022)
Group equivariant operators are a fundamental tool in the research on neural networks. In this paper we introduce and explore the concept of Group Equivariant Non-Expansive Operator (GENEO) associated with a symmetric function, making available a new method for the construction of non-linear GENEOs.